(untitled) (Journal of Oriental Studies, 2019)
The article analyzes the book of a native of the ancient Syrdarya city of Gent, an expert in Arabic grammar, Imam Taj ad-Din al-Zhendi “al-Makalid.” Taj ad-din Ahmed ibn Mahmoud ibn Omar al-Zhendi is considered to be one of the Arab grammar experts in the modern scientific community. The book “al-Makalid” is a commentary on the work of “al-Mishbah” by a famous linguist al-Muzaffar al-Muttarizi from Khorezm. Al-Makalid is notable for the ease of presentation of the analyzed textual material from the Qur’an, Hadith, Arabic literature, etc. The author dwells on the study of the basic syntactic rules of the Arabic language, a detailed analysis of the syntactic principles, forms of using words and phrases. The form of presentation of the material, which consists in the formulation of rules and principles by solving the questions of interest through a dialogue with the reader, is of great interest too. Key words: al-Zhendi, imam, scholar, “Al-Makalid”, Koranic texts, Arabic, grammar, syntax, word.